Pneumococcal and influenza vaccination coverage among at-risk adults: A 5-year French national observational study. Issue 33 (5th August 2022) - Wyplosz, Benjamin; Fernandes, Jérôme; Sultan, Ariane; Roche, Nicolas; Roubille, François; Loubet, Paul; Fougère, Bertrand; Moulin, Bruno; Duhot, Didier; Vainchtock, Alexandre; Raguideau, Fanny; Lortet-Tieulent, Joannie; et al.
Graphical abstract: Highlights: 4.5% out of 4.0 million adults at risk were vaccinated against pneumococcus. 92% of adults at risk visited a GP and 36% visited an outpatient specialist. From 10.3% in 2014 up to 18.8% in 2018 of immunocompromised patients were vaccinated against pneumococcus. From 12.9% in 2014 down to 2.9% in 2018 of people with a chronic medical condition were vaccinated. 43.6% of adults at risk of pneumococcal disease were vaccinated against influenza. Abstract: Introduction: The risk of developing pneumococcal infections increases with certain chronic conditions and in immunocompromised patients. We aimed to monitor pneumococcal vaccination coverage in at-risk patients and to examine factors associated with pneumococcal vaccination in France. Material and methods: In this annual cross-sectional study, at-risk patients were extracted between 2014 and 2018 from the National Health Insurance's (NHI) General scheme's claims database with their vaccine reimbursements. Descriptive analyses and a logistic model were performed to assess the influence of healthcare use and medical and demographic factors on pneumococcal vaccination. Results and discussion: In 2018, 4.5% of 4, 045, 021 at-risk adults were up to date with their pneumococcal vaccination. During the study period, the number of patients with chronic medical conditions (86% of 4, 045, 021) increased by 10.1%, but vaccination coverage decreased from 12.9% to 2.9%. The population with immunocompromised status (14% of 4, 045, 021) increased by 16.2% and vaccination coverage from 10.3% to 18.8%. Influenza vaccination coverage was much higher and stable (around 45.0%). Factors associated with pneumococcal vaccination were: immunocompromised status vs. having a chronic medical condition (odds ratio [OR] 4.72), influenza vaccination (OR 2.36–3.42), hepatitis B vaccination (OR 2.82), DTPolio vaccination (OR 1.52), ≥5 specialist physicians' visits (OR 1.17), and age above 74 (OR 1.12). Pneumococcal vaccine dispensing was extremely low (median of 9 per GP, 1 per specialist over 9 years) despite frequent healthcare visits. Conclusion: Pneumococcal and influenza vaccination coverage of adults at risk of pneumococcal disease fell well below public health expectations. Invitations for pneumococcal vaccination should be sent by the NHI to high-risk patients. Patient management protocols should include pneumococcal vaccination. Patients with multiple comorbidities are a high-priority population given the large potential health gains offered by pneumococcal vaccination. Commitment of both scientific societies and health authorities is urgently needed to increase vaccination coverage in at-risk populations.